Vector mechanics for engineers : (McGraw-Hill, 2007)
Vector Mechanics for Engineers: Statics marks the fiftieth anniversary of the Beer/Johnston series. Continuing in the spirit of its successful previous editions, the Eighth Edition provides conceptually accurate and thorough coverage together with a significant addition of new problems, including biomechanics problems, and the most extensive media resources available.